HIV Drug Resistance Mutations - Rizka Nadia; Dwitya Elvira; Raveinal (HM Publisher, 2022)
ART resistance, according to WHO, is the presence of one or more mutations in HIV that reduces the ability of certain drugs or drug groups to inhibit viral replication. According to the 2019 HIV Drug Resistance Report issued by the WHO, the prevalence of Antiretroviral Therapy (ART) drug resistance is 3%-29%. The prevalence of HIV drug resistance varies by country. In developed countries, the prevalence ranges from 6.6% to 11%. There are two types of resistance to ART: primary and secondary resistance. Primary resistance reflects the acquisition of drug-resistant strains in individuals who have recently been infected and have not received therapy. Secondary resistance occurs after treatment with ART. Resistance to antiretroviral therapy, mainly NRTIs, NNRTIs, and protease inhibitors, is caused by continuous inhibition of the HIV reverse transcriptase enzyme. World Health Organization (WHO) has recommended two NRTIs plus Lopinavir or Atazanavir as a second-line regimen for individuals who have failed treatment with efavirenz or dolutegravir; two NRTIs plus Darunavir and Lopinavir plus Raltegravir are recommended as an alternative due to cost constraints and the fact that Darunavir is unstable in moderately hot conditions.